SUBJECTIVE WELL-BEING DAN PRESTASI BELAJAR SISWA AKSELERASI MAN 3 PALEMBANG - Fara Hamdana; Alhamdu Alhamdu (Psikis : Jurnal Psikologi Islami, 2015)
The purpose of this study want to examine the subjective well-being condition of acceleration students program of MAN 3 Palembang, and want to know does has correlation between subjective well-being variable and learning achievement of students. The samples of this study chosen by cluster sampling and correlational quantitatif approach used in this study.The result found that subjective well-being condition of accelleration students program of class XI of MAN 3 Palembang there are in moderate position with values 64,3% or 18 students. Then, coefisient (r) is 0,877, with t count 9,035 > 2,055 (t table), F count 86,83 > 4,23 (F table), and p < 0,01. It means, there are have significant correlation between subjective well-being and learning achievement of students. Meanwhile, the value of determinant coeficient (R²)  0,769 showed that subjective well-being variable had contributed as predictor 76,9% toward learning achievement of students variable, and 23,1% as effect of others varibles.